Bispecific killer cell engager with high affinity and specificity toward CD16a on NK cells for cancer immunotherapy - Nikkhoi, Shahryar Khoshtinat; Li, Geng; Eleya, Suha; Yang, Ge; Vandavasi, Venu Gopal; Hatefi, Arash (Frontiers in Immunology, 2023)
The Fc region of monoclonal antibodies (mAbs) interacts with the CD16a receptor on natural killer (NK) cells with “low affinity” and “low selectivity”. This low affinity/selectivity interaction results in not only suboptimal anticancer activity but also induction of adverse effects. CD16a on NK cells binds to the antibody-coated cells, leading to antibody-dependent cell-mediated cytotoxicity (ADCC). Recent clinical data have shown that the increased binding affinity between mAb Fc region and CD16a receptor is responsible for significantly improved therapeutic outcomes. Therefore, the objective of this study was to develop a bispecific killer cell engager (BiKE) with high affinity and specificity/selectivity toward CD16a receptor for NK cell-based cancer immunotherapy. To engineer BiKE, a llama was immunized, then high binding anti-CD16a and anti-HER2 VHH clones were isolated using phage display. ELISA, flow cytometry, and biolayer interferometry (BLI) data showed that the isolated anti-CD16a VHH has high affinity (sub-nanomolar) toward CD16a antigen without cross-reactivity with CD16b-NA1 on neutrophils or CD32b on B cells. Similarly, the data showed that the isolated anti-HER2 VHH has high affinity/specificity toward HER2 antigen. Using a semi-flexible linker, anti-HER2 VHH was recombinantly fused with anti-CD16a VHH to create BiKE:HER2/CD16a. Then, the ability of BiKE:HER2/CD16a to activate NK cells to release cytokines and kill HER2+ cancer cells was measured. As effector cells, both high-affinity haNK92 (CD16+, V176) and low-affinity laNK92 (CD16+, F176) cells were used. The data showed that the engineered BiKE:HER2/CD16a activates haNK92 and laNK92 cells to release cytokines much greater than best-in-class mAbs in the clinic. The cytotoxicity data also showed that the developed BiKE induces higher ADCC to both ovarian and breast cancer cells in comparison to Trazimera™ (trastuzumab). According to the BLI data, BiKE:HER2/CD16 recognizes a different epitope on CD16a antigen than IgG-based mAbs; thus, it provides the opportunity for not only monotherapy but also combination therapy with other antibody drugs such as checkpoint inhibitors and antibody-drug conjugates. Taken together, the data demonstrate the creation of a novel BiKE with high affinity and specificity toward CD16a on NK cells with the potential to elicit a superior therapeutic response in patients with HER2+ cancer than existing anti-HER2 mAbs.